Weathering of Volcanic Rocks in Baturappe Formation and Its Implications for Foundation Planning of Pamukkulu Dam, South Sulawesi, Indonesia - Hendra Pachri; Ratna Husain; Adi Tonggiroh; Muhammad Yusril (Himpunan Ahli Teknik Tanah Indonesia, 2023)
The presence of weathered volcanic rocks in Pamukkulu area is important in determining the location and construction of the Pamukkulu main dam and plinth structure. In general, volcanic rocks have poor geotechnical characteristics due to varying degree of weathering, influence of groundwater, and systematic joints produced by cooling lava. This study aims to study the type and quality of weathered rock around the main dam and plinth area. First, mapping of surface geology was carried out. To evaluate the degree of weathering, rock resistivity data is used around the main dam area. Whereas for the plinth area, the bearing capacity of soil/rock is evaluated using Plate Bearing Test (PBT) and Standard Penetration Test (SPT). Bearing capacity obtained from PBT that were carried out on rock surface can be used to interpret rock weathering. In addition to SPT, the coring from rock drilling was also evaluated using Rock Quality Designation (RQD). It was found that the rock up to 20 m depth are of poor quality. It is recommended that the poor-quality rock is removed until moderately dense rock layer is found.